Practical mobile network planning and optimization for Thai smart cities: Towards a more inclusive globalization - Krishna Chimmanee; Suttisak Jantavongso (Research in Globalization, 2021)
Globalization has facilitated productivity gains and economic growth and for decades. It has helped integrate emerging economies, spread technology, knowledge, culture, and created an interconnected global community. Smart cities depend on a robust and flexible mobile network foundation, and yet, Thailand is leading the way in the ASEAN. Using Thailand as a case study, this paper presents a practical mobile network planning and optimization framework (PMNPO) that's workable for the fourth-generation up to sixth-generation networks in smart cities, especially in an industrial estate. While theoretical frameworks play a vital role in optimizing network performance, such frameworks may not be practical enough. This study applies a mixed quantitative research method on actual applications (case studies) and qualitative research. The PMNPO is a management function of pseudo-codes. A workable cost-sharing model for mobile networks consists of CAPEX, OPEX, feasibility study, and site value management (mobile network operators). The fair factor (0.2), the payback (5 years), the NPV (0.5 million), and the IRR (20%) reveal a promising financial prospect. The PMNPO is practical for Thailand, with a mean acceptance rate of 4.83. Therefore, the findings support stakeholders, policymakers, and decision-makers, in setting telecommunication policies. The results can apply to other developing countries or catalyze a similar research type.
Keywords: 330; Mobile network; Optimization; Planning; Techno-economic; Smart cities; Thailand